A Four-dimensional Approach to Medical Image Retrieval - Chbeir, R.; Amghar, Y.; Flory, A. (Methods of Information in Medicine, 2001)
Image retrieval is faced with different problems. Few proposed solutions consider the heterogeneity of user competence (e.g. physicians, researchers, students, etc.) and the necessity of a high expressive power for medical image description. This paper presents a solution designed for medical imaging retrieval. It consists of providing a four-dimensional approach able to integrate different views of the medical image, to deal with complex medical queries. Via use of the Spatial Knowledge Model, we propose hybrid (textual and visual) and customizable interfaces, appropriate for non-computer scientist users. Our prototype, accessible through the Web, has been tested by a group of medical students and physicians and gives very satisfactory results.
Keywords: Medical Image Retrieval; Spatial Knowledge Model